Optimization of Arabic Language Learning through Probing Prompting with Instagram Application - Widi Astuti; Mega Primaningtyas; Ameliani Ameliani; Syaifuddin Zuhdi (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: This study aims to evaluate the effectiveness of the probing prompting technique in learning Arabic through the Instagram platform at the MBS Jatinom Islamic Boarding School, Klaten. With a descriptive qualitative approach, this study involved teachers and students as the main subjects. Data were obtained through observation, interviews, documentation, and questionnaires. Observations focused on learning interactions using Instagram features, such as stories and live streaming, while interviews and questionnaires explored teachers' and students' perceptions regarding the application of the probing prompting method in the teaching and learning process. The results showed that the application of probing prompting combined with the use of Instagram significantly improved Arabic language skills, especially in speaking and listening aspects. Students in the experimental group showed greater improvement than the control group, with better learning outcomes and a deeper understanding of the material. The use of Instagram as a learning medium also allows for more flexible and dynamic interactions between teachers and students, expanding the scope of learning from the classroom to the digital realm. The conclusion of this study confirms that the probing prompting method through Instagram can be an effective learning strategy in improving Arabic language skills. However, there are challenges that need to be considered, such as access to technology and user readiness to utilize social media optimally. Integration between traditional learning methods and digital technology can increase motivation, participation, and the quality of learning outcomes, making learning more relevant to the needs of the times.